Psychosocial Response to National Security - Singh, Jitendra Kumar (Defence Life Science Journal, 2021)
National security is perhaps one of the key areas of research which receives continuous attention from the scholars of strategic studies, military science, and of course some of the disciplines of social science such as political science and international relation. One way of pursuing interest in national security is to delve the threat perception which emanates from across the border and is likely to influence socio-political sphere of the nation. On the other hand, the diversity in the socio-cultural landscape of the nation characterized by ethnicity and linguistic based sub-national identities is equally important so far as enriching one’s knowledge base in the domain of internal security is concerned. Within the realm of psychology, military psychology is possibly one sub-discipline which tries to address this gap. However, psychology is yet to receive a space in the intellectual terrain of studies on national security.